Analysis of The Influence of Taxes, Tunnelling Incentives, and Exchange Rate on Transfer Pricing - Gracela Abigail Rokot; Luh Nadi (Komunitas Dosen Indonesia, 2024)
This study aims to investigate effect of taxes, tunnelling incentives and exchange rates on Transfer Pricing in Manufacturing Companies Basic Industry and Chemical Sectors listed on the Indonesian Stock Exchange. Determining the research sample used a purposive sampling method and obtained a research sample of 11 companies. The analysis method uses panel data regression techniques with Random Effect Models using EViews. The results of this research prove that together the tax variables, Tunnelling Incentive and Exchange Rate have a significant effect on transfer pricing. Tax has no significant effect on transfer pricing, Tunnelling Incentive has a significant effect on transfer pricing and the Exchange Rate has a significant effect on transfer pricing. This research provides evidence that an increasing exchange rate will influence a company's decision to carry out transfer pricing, and the exchange rate has an impact on a country's trade balance. Tunneling and transfer pricing present significant challenges that require coordinated efforts from corporations, regulators, and international bodies. By strengthening corporate governance, enhancing regulatory frameworks, and fostering transparency, stakeholders can mitigate the risks associated with these practices and promote a fair and efficient business environment. Keywords: Tax; Tunnelling Incentives; Exchange Rate; Transfer Pricing.